The Value Dimension of Public Opinion in Ukraine During the Full Scale War and Its Role for Post-War Reconstruction - Дембіцький, Сергій; Dembitskyi, Serhii; Кириченко, Роман; Kyrychenko, Roman; Сальнікова, Світлана; Salnikova, Svitlana; Сидоров, Микола; Sydorov, Mykola (Волинський національний університет імені Лесі Українки (43025, м. Луцьк, просп. Волі, 13) Київський національний університет імені Тараса Шевченка (03680, м. Київ, просп. Акад. Глушкова, 4д), 2022)
The article is devoted to the relevance of the social values of liberal-democratic societies during the war, their structural features, and their role in the post-war reconstruction of Ukraine. The corresponding values include safety, diversity, selectivity, normativity, freedom, equality, order, stability, development, independence, and strength. The empirical part of the study is based on the results of an online survey conducted in July 2022. The sample size is 2,350 respondents (women – 51,3 %, men – 48,7 %, average age – 37,3 years). The structure of the sample repeats the structure of the urban population of Ukraine aged 18 to 55 at the beginning of the war in settlements with 50 thousand inhabitants or more for all regions, except the following groups: 1) population on the territories of Donetsk and Luhansk regions temporarily occupied at the beginning of the war, as well as AR Crimea; 2) population on other territories of Luhansk region; 3) population on the territories of Kherson region. The ranking of societal values (Condorcet method) was established: safety (80,5 %), strength (63,8 %), order (61,3 %), normativity (58,9 %), equality (53,6 %), liberty (48,4 %), stability (44,0 %), independence (37,4 %), development (35,6 %), diversity (34,1 %), selectivity (32.3 %). Two clusters are identified in the structure of societal values. The first includes order, safety, diversity, selectivity, normativity, liberty, and equality. In general, this value cluster emphasizes the need for internal balance, which is a fundamental guarantee of national resilience during a large-scale war, as it preserves the ability of society to generate additional resources needed by the state. The second value cluster includes strength, development, independence, and stability. This substructure is related to that part of national resilience responsible for responding to external crises and challenges. Forecasts were made regarding the priority relevance of almost all societal values in the period of post-war reconstruction: 1) safety due to the damage caused by the war to the population and territories of Ukraine; 2) strength due to the successes of Ukraine in the defense and diplomatic spheres; 3) order due to the inadmissibility of cleavage narratives in society; 4) normativity due to the request for implementation of the rule of law; 5) equality due to the need for support of broad sections of the population from the state; 6) liberty due to the need of gradual easing of restrictions that arose due to the war; 7) stability due to the constant demand for it in peacetime; 8) development due to its fundamental importance for the national subjectivity of Ukraine; 9) diversity due to modern landmarks of civilizational development; 10) selectivity due to the need for effective management decisions.

Стаття присвячена актуальності соцієтальних цінностей ліберально-демократичних суспільств під час війни, їх структурним особливостям та ролі у післявоєнній відбудові України. Емпірична частина дослідження базується на результатах онлайн опитування (липень 2022). Структура вибірки (N=2350; жінки – 51,3 %, чоловіки – 48,7 %) повторює структуру міського населення України у віці від 18 до 55 років на початок війни в населених пунктах від 50 тис. жителів та більше, за виключенням окупованих регіонів. Встановлено рейтинг соцієтальних цінностей (метод Кондорсе): безпека (80,5 %), сила (63,8 %), порядок (61,3 %), нормативність (58,9 %), рівність (53,6 %), свобода (48,4 %), стабільність (44,0 %), самостійність (37,4 %), розвиток (35,6 %), різноманіття (34,1 %), селективність (32,3 %). У структурі соцієтальних цінностей ідентифіковано два кластери. Перший кластер упредметнює потребу внутрішньої рівноваги, що є принциповою запорукою національної стійкості під час російсько-української війни, оскільки зберігає можливість суспільства генерувати додаткові ресурси, необхідні державі. Другий кластер пов’язаний з тією частиною національної стійкості, що відповідає за реагування на зовнішні кризи та виклики. Зроблено прогноз щодо першочергової актуальності майже усіх соцієтальних цінностей у період післявоєнної відбудови, за виключенням цінності самостійності (останнє пов’язано з необхідністю інтеграції до західних політичних та оборонних структур).
Ціннісний вимір громадської думки в Україні під час повномасштабної війни та його значення для післявоєнної відбудови
Keywords: Russo-Ukrainian war; societal values; the hierarchy of values; value structure; Condorcet method; російсько-українська війна; соцієтальні цінності; ієрархія цінностей; ціннісна структура; метод Кондорсе; 316